Elevated phosphorus impedes manganese acquisition by barley plants - Pedas, Pai; Husted, Søren; Skytte, Kristian; Schjoerring, Jan K. (Frontiers in Plant Science, 2011)
The occurrence of manganese (Mn) deficiency in cereal crops has increased in recent years. This coincides with increasing phosphorus (P) status of many soils due to application of high levels of animal manure. In order to test the hypothesis that elevated P my lead to Mn deficiency we have here conducted a series of hydroponics and soil experiments examining how the P supply affects the Mn nutrition of barley. Evidence for a direct negative interaction between P and Mn during root uptake was obtained by online inductively coupled plasma mass spectrometry (ICP-MS). Addition of a pulse of KH2PO4 rapidly and significantly reduced root Mn uptake, while a similar concentration of KCl had no effect. Addition of a similar P pulse to the same nutrient solution without plants did not affect the concentration of Mn, revealing that no precipitation of Mn-P species was occurring. Barley plants growing at a high P supply in hydroponics with continuous replenishment of Mn had up to 50% lower Mn concentration in the youngest leaves than P limited plants. This P-induced depression of foliar Mn accelerated the development of Mn deficiency as evidenced by a marked change in the fluorescence induction kinetics of chlorophyll a. Also plants growing in soil exhibited lower leaf Mn concentrations in response to elevated P. In contrast, leaf concentrations of Fe, Cu and N increased with the P supply, supporting that the negative effect of P on Mn acquisition was specific rather than due to a general dilution effect. It is concluded that elevated P supply directly interferes with Mn uptake in barley roots and that this negative interaction can induce Mn deficiency in the shoot. This finding has major implications in commercial plant production where many soils have high P levels.